2021
DOI: 10.14295/bds.2021.v24i3.2494
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Preparation Design, Restorative Material and Load Direction on The Stress Distribution of Ceramic Veneer in Upper Central Incisor

Abstract: Objective: Evaluate the effect of four preparation designs, two ceramic materials, and two occlusion contact types on the stress distribution of ceramic veneer in upper central incisor. Material and methods:  3D-models were performed in the modeling software containing enamel, dentin, pulp, periodontal ligament and a base of polyurethane resin. The designs were modeled and exported to the computer aided engineering software to perform the static structural analysis. For the mesh, a total of 155429 tetrahedron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…These observations are consistent with the study [33] which showed that the narrow structure at the crown tip causes high stresses and bending in the crown. The present numerical results also match other studies where high stresses were reported on the enamel surface within top 1/3 rd region of the crown [19,36,45,48].…”
Section: Effect Of Loading Anglesupporting
confidence: 91%
“…These observations are consistent with the study [33] which showed that the narrow structure at the crown tip causes high stresses and bending in the crown. The present numerical results also match other studies where high stresses were reported on the enamel surface within top 1/3 rd region of the crown [19,36,45,48].…”
Section: Effect Of Loading Anglesupporting
confidence: 91%
“…Finite element studies have concluded that the combination of ceramic and cement can affect the performance of ceramic veneers in upper central incisors. 37 45 46 In addition, Tribst et al 45 evaluated occlusal veneers in posterior teeth and concluded that than the higher elastic modulus of the material than higher the stress magnitude. Corroborating with that, in the present study the PICN samples showed lower stress concentration in relation to the restoration, but not in relation to the cement layer.…”
Section: Discussionmentioning
confidence: 99%
“…For dental composites, in order to effectively reduce the polymerization stress during resin placement, a material with low post-gel shrinkage must be associated to a relatively low elastic modulus [2]. This can be justified because, in summary, the higher the elastic modulus of the restorative material, the smaller the deformation of dental structures under the same stress [36]. However, a reduction in the dental composite elastic modulus could lead to low hardness and low wear strength.…”
Section: Discussionmentioning
confidence: 99%
“…After that, the software determines by means of a numerical calculation from the acoustic signal that was captured in order to obtain the frequency spectrum (fast Fourier transform). Based on this, the dynamic elastic modulus was determined using the ASTM standard, which considers the specimen geometry, mass, dimensions, and frequencies obtained using the equipment [35,36]. The characterization of the Poisson ratio using impulse excitation technique occurred indirectly.…”
Section: Elastic Modulus and Poisson Ratiomentioning
confidence: 99%